PENGARUH TINGKAT PENGETAHUAN TENTANG BERLALU LINTAS, TINGKAT PENDIDIKAN DAN USIA TERHADAP MOTIVASI KEPATUHAN DALAM BERLALU LINTAS PADA WARGA - Endang Dwi Ningsih; Ni Ayu Rai Krishanandini R.D. (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2019)
Background: Based on a WHO’s research in 2011, traffic accidents are included among the top-10 of the death causes in Indonesia. The traffic accidents are influenced by the knowledge lacks of the accidents impact for health. The proper traffic knowledge, education and age level of someone influences in motivation keeping safer and healthier themself by doing the right way on traffic. Regarding above, it is necessary to conduct a research about the effect of the traffic knowledge, education and age level on the motivation to compliance the traffic properly to the citizen. Research Objective : to determine the influence of the traffic knowledge, education and age level on the motivation to compliance the traffic properly to the citizen. Research Subjects : the study sampling of 200 peoples residing in the are of The Surakarta Traffic Department office by using Saturated sampling techniques. Results : by the Bivariate test shows that there was an influence on the traffic knowledge level towards the obedience motivation in proper traffic (p = 0.000, p < 0.005), there was no influence on the education level towards the obedience motivation in proper traffic (p = 0.437, p > 0.005), and there was an influence on the age level towards the obedience motivation in proper traffic (p = 0.000, p < 0.005). Conclusion : that the age variable and the traffic knowledge level were together influence toward the obedience motivation in proper traffic by 53,3% and the 46.7% remaining was influenced by other variables that have not been studied. Keywords: The obedience motivation in proper traffic, the traffic knowledge level, the education and age level.Background: Based on a WHO’s research in 2011, traffic accidents are included among the top-10 of the death causes in Indonesia.The traffic accidents are influenced by the knowledge lacks of the accidents impact for health. The proper traffic knowledge, education and age level of someone influences in motivation keeping safer and healthier themself by doing the right way on traffic. Regarding above, it is necessary to conduct a research about the effect of the traffic knowledge, education and age level on the motivation to compliance the traffic properly to the citizen.Research Objective : to determine the influence of the traffic knowledge, education and age level on the motivation to compliance the traffic properly to the citizen.Research Subjects : the study sampling of 200 peoples residing in the are of The Surakarta Traffic Department office by using Saturated sampling techniques.Results : by the Bivariate test shows that there was an influence on the traffic knowledge level towards the obedience motivation in proper traffic (p = 0.000, p < 0.005), there was no influence on the education level towards the obedience motivation in proper traffic (p = 0.437, p > 0.005), and there was an influence on the age level towards the obedience motivation in proper traffic (p = 0.000, p < 0.005).Conclusion : that the age variable and the traffic knowledge level were together influence toward the obedience motivation in proper traffic by 53,3% and the 46.7% remaining was influenced by other variables that have not been studied. Keywords: The obedience motivation in proper traffic, the traffic knowledge level, the education and age level.